THE INFLUENCE OF THE APPLICATION OF THE PROBLEM-BASED LEARNING MODEL ON THE LEARNING OUTCOMES AT SMPN 2 KOTAGAJAH - Martono, Martono (Teaching English as a Foreign Language Overseas Journal, 2022)
ABSTRACT The main problem in this study is whether the application of the problem-based learning model affects the English studies learning outcomes of grade VIII students of SMPN 2 Kotagajah. This study aims to determine the influence of the application of the problem-based learning model on social science learning outcomes in grade VIII students of SMPN 2 Kotagajah. This type of research is a true experimental study of the Posttest Only Control Group Design form involving two classes. The subjects in this study were grade VIII students of SMPN 2 Kotagajah which consisted of two groups, namely the control group of 32 students and the experimental group of 32 students. The control group is a conventionally taught group while the experimental group is a group taught with a problem-based learning (PBL) model. The results of descriptive statistical analysis of the use of problem-based learning models on student Social Science learning outcomes have a positive effect, student Social Science learning outcomes using problem-based learning models show better learning outcomes than before the problem-based learning model was applied. The results of inferential statistical analysis using the t-test formula, it is known that the calculated value of t-Count is 9.01 with a frequency of db = 32–1 = 31, at a significance level of 5% obtained t-Table = 2.04. So, t Calculate > t table or null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. This proves that there is an influence in applying the problem-based learning model to the learning outcomes of English students in grade VIII SMPN 2 Kotagajah